Recessions and potential output: disentangling measurement errors, supply shocks, and hysteresis effects* - Dovern, Jonas; Zuber, Christopher (The Scandinavian journal of economics, 2020)
This paper investigates expert revisions of potential output (PO) estimates following recessions. Using data from the Organisation for Economic Co-operation and Development (OECD), we show that downward revisions are substantial, permanent, and mostly driven by supply shocks. In contrast, PO estimates do not significantly react to demand shocks. Revisions are also partly caused by mismeasurement of PO before recessions. In particular, we show that the length of the preceding boom and pre-recession values of the current account balance and credit volumes are correlated with post-recession PO revisions. Our results call for improved methods for estimating PO and provide evidence against the existence of substantial hysteresis following demand shocks.
First published: 24 May 2019
Gesehen am 13.01.2021